2013
DOI: 10.1186/gb-2013-14-12-r141
|View full text |Cite
|
Sign up to set email alerts
|

Obligate mutualism within a host drives the extreme specialization of a fig wasp genome

Abstract: BackgroundFig pollinating wasps form obligate symbioses with their fig hosts. This mutualism arose approximately 75 million years ago. Unlike many other intimate symbioses, which involve vertical transmission of symbionts to host offspring, female fig wasps fly great distances to transfer horizontally between hosts. In contrast, male wasps are wingless and cannot disperse. Symbionts that keep intimate contact with their hosts often show genome reduction, but it is not clear if the wide dispersal of female fig … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
97
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(105 citation statements)
references
References 79 publications
7
97
0
1
Order By: Relevance
“…Through the application of transcriptomic approaches we were able to determine that endophytophagous wasps share many homologous venoms with parasitoids, which suggests that the evolution of plant endoparasitism in Megastigmus may not have completely relied on wholesale innovations; sequencing the M. spermotrophus genome would help resolve this more clearly. On this note, a recent analysis of the genome of the fig wasp Ceratosolen solmsi did not identify any unique genes or gene family expansions related to host manipulation compared with N. vitripennis (Xiao et al ., ), which also supports the idea that endophytophagous hymenopteran lineages have probably adapted the parasitoid venom machinery for manipulating plants.…”
Section: Discussionsupporting
confidence: 76%
“…Through the application of transcriptomic approaches we were able to determine that endophytophagous wasps share many homologous venoms with parasitoids, which suggests that the evolution of plant endoparasitism in Megastigmus may not have completely relied on wholesale innovations; sequencing the M. spermotrophus genome would help resolve this more clearly. On this note, a recent analysis of the genome of the fig wasp Ceratosolen solmsi did not identify any unique genes or gene family expansions related to host manipulation compared with N. vitripennis (Xiao et al ., ), which also supports the idea that endophytophagous hymenopteran lineages have probably adapted the parasitoid venom machinery for manipulating plants.…”
Section: Discussionsupporting
confidence: 76%
“…Our method retrieved all regions of previously reported in N. vitripennis genome. Using C. solmsi partial mitochondrial genome which only contain 11 of 13 mitochondrial proteins, we found 176 NUMTs summing up to 53,962 bp in the C. solmsi genome (Xiao et al, 2013), which is around fifteen-fold greater than P. puparum . These results indicate that the shorter total NUMTs length detected in P. puparum is not caused by a method difference.…”
Section: Resultsmentioning
confidence: 95%
“…It has been reported that NUMT length is positively correlated with genome size, suggesting potential roles of non-coding DNA gain and loss in NUMT accumulation (Hazkani-Covo et al, 2010; Song et al, 2013). However, genome size can’t explain fewer NUMTs in P. puparum , as assembled genome size of P. puparum is larger than those of N. vitripennis, A. mellifera and C. solmsi (Weinstock et al, 2006; Werren et al., 2010; Xiao et al, 2013). In addition, fewer detected NUMTs in P. puparum is not caused by faster evolutionary rate of P. puparum mitochondrial genome, as slower mitochondrial protein substitution rates were shown in P. puparum than N. vitripennis and C. solmsi (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, a definitive proof of cospeciation resulting from co‐evolution (e.g., rather than from similar responses to geographic isolation) would require demonstrating a match between the signal genes in figs (scent pathways) and receiver genes in wasps (olfactory receptors; Segar, Volf, Sisol, Pardikes, & Souto‐Vilarós, ). While the genomic data for such analyses are becoming increasingly available (Mori et al, ; Xiao et al, ) they have yet to be compiled for our study system. Genomic matching of the corresponding genes in plants and pollinators stands out as the necessary next step toward the mechanistic understanding of cospeciation patterns (Segar et al, ).…”
Section: Discussionmentioning
confidence: 99%